Pengawasan dan Peredaran Narkoba Antar Negara - Sri Iin Hartini; Salesius Jemaru (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2018)
The purpose of this research is to know the extent of supervision and distribution of drugs among the people of both countries (Indonesia and PNG). In conducting the KKN-PPM program is in the form of legal counseling and socialization to the public about the danger of drug distribution and control as well as the legal impact. The outcomes to be achieved after legal counseling are reduced drug users and increased legal awareness as well as the participation of local communities and Local Government to improve supervision of narcotics circulation between the two countries.